The Potential of Non-thermal Plasmas in the Preparation of Supported Metal Catalysts for Fuel Conversion in Automotive Systems: A Literature Overview - Santos, Andrey M. dos; Catapan, Rafael C.; Duarte, Diego A. (Frontiers in Mechanical Engineering, 2020)
The growing demand for energy worldwide and the extensive use of fossil fuels have resulted in severe environmental problems such as air pollution and the accumulation of greenhouse gases in the atmosphere. In this scenario, both new energy sources and more efficient energy conversion processes have been deeply studied. Heterogeneous catalysis is currently widely used for hydrogen production due to its higher selectivity and conversion compared to other processes. Although the use of catalysts is fundamental for green chemistry, their production through traditional methods is less environmentally friendly. Nonetheless, in order to obtain more efficient supported metal catalysts, interest in using non-thermal plasma as a pretreatment or synthesis technique is increasing. Thus, the present article aims at summarizing and briefly discussing the relevant research results on this subject, elucidating the advantages and disadvantages of using non-thermal plasmas in the preparation of supported metal catalysts. Aspects such as morphology, the chemical composition of the catalytic surface, crystallographic phases, average size and dispersion of crystallites, specific surface area, and metal–support interaction have been analyzed. The use of plasma-assisted techniques contributes to the synthesis of supported metal catalysts with smaller, more dispersed, and strongly bonded active particles, resulting in higher catalytic activity, conversion rate, selectivity, and durability. In addition, plasma allows the synthesis of supported metal catalysts to be enhanced by reducing the process time, the use of hazardous substances, and the temperature required.